Efficacies and ADME properties of redox active methylene blue and phenoxazine analogues for use in new antimalarial triple drug combinations with amino-artemisinins - Watson, Daniel J.; Laing, Lizahn; Petzer, Jacobus P.; Wong, Ho Ning; Parkinson, Christopher J.; Wiesner, Lubbe; Haynes, Richard K. (Frontiers in Pharmacology, 2024)
Efforts to develop new artemisinin triple combination therapies effective against artemisinintolerant strains of Plasmodium falciparum based on rational combinations comprising artemisone or other amino-artemisinins, a redox active drug and a third drug with a different mode of action have now been extended to evaluation of three potential redox partners. These are the diethyl analogue AD01 of methylene blue (MB), the benzo[α]phenoxazine PhX6, and the thiosemicarbazone DpNEt. IC50 values in vitro against CQ-sensitive and resistant P. falciparum strains ranged from 11.9 nM for AD01 to 41.8 nM for PhX6. PhX6 possessed the most favourable pharmacokinetic (PK) profile: intrinsic clearance rate CLint was 21.47 ± 1.76 mL/min/kg, bioavailability was 60% and half-life was 7.96 h. AD01 presented weaker, but manageable PK properties with a rapid CLint of 74.41 ± 6.68 mL/min/kg leading to a half-life of 2.51 ± 0.07 h and bioavailability of 15%. DpNEt exhibited a half-life of 1.12 h and bioavailability of 8%, data which discourage its further examination, despite a low CLint of 10.20 mL/min/kg and a high Cmax of 6.32 µM. Efficacies of AD01 and PhX6 were enhanced synergistically when each was paired with artemisone against asexual blood stages of P. falciparum NF54 in vitro. The favourable pharmacokinetics of PhX6 indicate this is the best partner among the compounds examined thus far for artemisone. Future work will focus on extending the drug combination studies to artemiside in vitro, and conducting efficacy studies in vivo for artemisone with each of PhX6 and the related benzo[α]phenoxazine SSJ-183.